Plasma cytokines and risk of coronary heart disease in the PROCARDIS study - Clarke, R; Valdes-Marquez, E; Hill, M; Gordon, J; Farrall, M; Hamsten, A; Watkins, H; Hopewell, J (BMJ Publishing Group, 2018)
Objective The aims of the study were to examine the associations of plasma levels of five cytokines (interleukin (IL)-6, IL-5, interferon-gamma (IFN-γ), tumour necrosis factor-alpha (TNF-α) and IL-6 receptor (IL-6R)) and C reactive protein (CRP) with risk of coronary heart disease (CHD). Methods: In a case–control study of 931 CHD cases and 974 controls, logistic regression was used to estimate the OR and 95% CI of CHD for extreme thirds of biomarkers after adjustment for established risk factors. Sensitivity analyses were conducted in non-statin and in non-aspirin users. Results: Plasma levels of CRP were moderately correlated with IL-6 (r=0.45) in controls, but more weakly correlated with other cytokines. Likewise, all other cytokines were only weakly correlated with each other. After adjustment for established risk factors, the ORs (95% CI) for CHD comparing extreme thirds of cytokine levels (defined in controls) were 2.53 (1.86 to 3.43) for IL-6, 1.46 (1.11 to 1.93) for IL-5 and 1.46 (1.09 to 1.95) for IFN-γ, respectively. However, neither TNF-α, IL-6R nor CRP was significantly associated with CHD. After further adjustment for the associated cytokines, only IL-5 (1.34; 1.00 to 1.80) and IL-6 (2.39; 1.73 to 3.30) remained significantly associated with CHD. The risk associations of cytokines in non-users of statins or aspirin were comparable with the overall population. Conclusions: This study confirmed the importance of IL-6 as the most strongly associated cytokine with CHD risk, but also demonstrated novel and independent associations of IL-5 with CHD that warrant further investigation using larger panels of cytokines.